Load altering attack-tolerant defense strategy for load frequency control system. (15th December 2020) - Chen, Chunyu; Cui, Mingjian; Fang, Xin; Ren, Bixing; Chen, Yang
Abstract: Cyber attacks become emerging threats to every information-oriented energy management system. By violating the cyber systems, the hacker can disrupt the security and stability due to the strong coupling between the cyber and physical facilities. In this paper, one type of cyber attacks designated as the load altering attack is studied for the power system frequency control, and corresponding defense strategies are proposed to improve the frequency control performance. Considering the difficulty of the application of model-based controller into large-scale power systems, a novel model-free defense framework is for the first time presented. Under this framework, both active defense and passive defense strategies are designed. The former assumes that the defender has the initiative to learn different attack scenarios. Adaptive defense strategies are implemented using the online attack identification information and off-line trained strategy pool. The latter assumes that the defender passively tolerates various attack scenarios via the pre-trained off-line strategy. Both approaches prove to be effective through validation based on the IEEE benchmark systems. The proposed defense framework and defense strategies can be extended to other energy control systems to enhance their attack tolerance capability. Highlights: A load altering attack-tolerant power system frequency control framework is proposed. The philosophy of active and passive defense is used to design the attack-tolerant frequency control strategies. The reinforcement learning techniques are adopted to design the model-free frequency controller for complex power systems. The simulation results via benchmark systems show the effectiveness of load altering attack attenuation.